Composite solid electrolyte, preparation method thereof and solid-state battery

By providing a cladding layer containing sulfone polymer, lithium salt and/or ionic liquid on the surface of the electrolyte matrix of the solid electrolyte, the oxidation problem caused by the narrow electrochemical window of the solid electrolyte is solved, and the cycling performance of the battery is improved.

CN119447425APending Publication Date: 2025-02-14ZHEJIANG INTELLIGENT TRANSPORTATION TECHNOLOGY INNOVATION CENTER +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411646425.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Due to the narrow electrochemical window of the existing solid electrolyte, it is easy to be oxidized at the positive electrode interface, forming an intermediate layer with low ionic conductivity, increasing the interface impedance, and affecting the cycling performance of the battery.

Method used

The cladding layer is provided on the surface of the electrolyte matrix of the sulfide electrolyte, halide electrolyte or oxide electrolyte, which includes sulfone polymers, lithium salts and/or ionic liquids, through which high oxidation resistance and high ion conduction of these materials , improve the oxidation resistance and ion conduction effect of the electrolyte.

Benefits of technology

By improving the oxidation resistance and ion conduction effect of solid electrolytes, the interface problems between the solid electrolyte and the electrode are alleviated, and the cycling performance of the battery is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005139810120000141
    Figure BDA0005139810120000141
  • Figure BDA0005139810120000151
    Figure BDA0005139810120000151
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a composite solid electrolyte, a preparation method thereof and a solid-state battery. The provided composite solid electrolyte comprises: an electrolyte matrix comprising at least one of a sulfide electrolyte, a halide electrolyte or an oxide electrolyte; the coating layer is coated on at least part of the surface of the electrolyte matrix, and the coating layer comprises a sulfone polymer and lithium salt and / or ionic liquid. The preparation method of the composite solid electrolyte comprises the following steps: providing a coating material solution which comprises a sulfone monomer and a lithium salt and / or an ionic liquid; and mixing the coating material solution with an electrolyte matrix, an initiator and a solvent, heating, stirring and drying to form a coating layer on at least the surface of the electrolyte matrix, thereby obtaining the composite solid electrolyte. The oxidation resistance of the electrolyte can be improved, the ion conduction effect of the electrolyte can be improved, and the cycle stability of the battery can be guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a composite solid electrolyte and a preparation method thereof, and a solid-state battery. Background Art

[0002] Solid-state batteries inherit the advantages of traditional lithium batteries and have outstanding advantages such as better safety and high energy density. At present, in solid-state batteries, the main solid electrolytes studied include polymers, oxides, sulfides and halides. Although solid-state batteries have the advantages of high safety and high energy density, the traditional solid electrolytes used at this stage still have some shortcomings that need to be solved urgently. One of the more prominent points is the interface problem between the solid electrolyte membrane and the electrode. Specifically, some solid electrolytes, such as sulfide solid electrolytes, have a narrow electrochemical window and are easily oxidized at the positive electrode interface to form an intermediate layer with low ionic conductivity, which increases the interface impedance and has an adverse effect on the battery's cycle performance.

[0003] In view of this, this application is hereby filed. Summary of the invention

[0004] In view of this, the present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides a composite solid electrolyte and a preparation method thereof and a solid-state battery, which are beneficial to improving the oxidation resistance of the solid electrolyte, improving the ion conduction effect of the electrolyte, alleviating the interface problem between the solid electrolyte and the electrode, and thus improving the cycle performance of the battery.

[0005] In order to solve the above technical problems, this application is implemented as follows:

[0006] According to one aspect of the present application, an embodiment of the present application provides a composite solid electrolyte, characterized in that the composite solid electrolyte comprises:

[0007] an electrolyte matrix, the electrolyte matrix comprising at least one of a sulfide electrolyte, a halide electrolyte, or an oxide electrolyte; and

[0008] The coating layer is coated on at least a portion of the surface of the electrolyte matrix, the coating layer comprises a sulfone polymer, and the coating layer further comprises a lithium salt and / or an ionic liquid.

[0009] In addition, the composite solid electrolyte according to the present application may also have the following additional technical features:

[0010] In some embodiments, the sulfone polymer is formed by polymerizing a sulfone monomer, and the sulfone monomer includes at least one of methyl vinyl sulfone, ethyl vinyl sulfone, phenyl vinyl sulfone, divinyl sulfone or phenyl vinyl sulfoxide.

[0011] In some of the embodiments, the lithium salt comprises a fluorine-containing lithium salt.

[0012] In some embodiments, the ionic liquid includes at least one of an imidazole ionic liquid, a quaternary amine ionic liquid, a quaternary phosphonium ionic liquid, a pyridine ionic liquid, a pyrrolidine ionic liquid or a piperidine ionic liquid.

[0013] In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethylsulfonyl)imide, lithium oxalate, and lithium bis(trifluoromethylsulfonyl)imide.

[0014] In some embodiments, the cation of the ionic liquid includes at least one of quaternary ammonium salt ions, quaternary phosphonium salt ions, imidazolium salt ions and pyrrole salt ions, and the anion of the ionic liquid includes at least one of halogen ions, tetrafluoroborate ions or hexafluorophosphate ions.

[0015] In some embodiments, the coating layer has a thickness of ≤500 nm.

[0016] In some of the embodiments, in the composite solid electrolyte, the mass proportion of the coating layer is 0.1% to 50%.

[0017] According to another aspect of the present application, an embodiment of the present application provides a method for preparing a composite solid electrolyte, the method comprising the following steps:

[0018] Providing a coating material solution, wherein the coating material solution includes a sulfone monomer, and a lithium salt and / or an ionic liquid;

[0019] The coating material solution is mixed with an electrolyte matrix, an initiator and a solvent, and after heating, stirring and drying, a coating layer is formed on at least the surface of the electrolyte matrix to obtain a composite solid electrolyte.

[0020] In some embodiments, the concentration of the coating material solution is 0.5 to 2 mol / L.

[0021] In some embodiments, the sulfone monomer includes at least one of methyl vinyl sulfone, ethyl vinyl sulfone, phenyl vinyl sulfone, divinyl sulfone or phenyl vinyl sulfoxide.

[0022] In some of the embodiments, the lithium salt comprises a fluorine-containing lithium salt.

[0023] In some embodiments, the ionic liquid includes at least one of an imidazole ionic liquid, a quaternary amine ionic liquid, a quaternary phosphonium ionic liquid, a pyridine ionic liquid, a pyrrolidine ionic liquid or a piperidine ionic liquid.

[0024] In some embodiments, the initiator includes at least one of azobisisobutyronitrile, dimethyl azobisisobutyrate, azobisisoheptanenitrile, ammonium persulfate, benzoyl peroxide, tert-butyl benzoyl peroxide, or methyl ethyl ketone peroxide.

[0025] In some preferred embodiments, the initiator is selected from azobisisobutyronitrile.

[0026] In some embodiments, the solvent includes a nitrile organic solvent and / or an alcohol organic solvent, the nitrile organic solvent includes at least one of succinonitrile, adiponitrile, glutaronitrile or acetonitrile, and the alcohol organic solvent includes at least one of methanol, ethanol, propanol or butanol.

[0027] In some preferred embodiments, the solvent is selected from acetonitrile.

[0028] In some embodiments, the heating and stirring conditions include: stirring at a rotation speed of 400 rpm to 1000 rpm for 10 h to 24 h in an environment where the dew point temperature is lower than -50°C.

[0029] In some of the embodiments, after the heating and stirring and before the drying, a step of heating to volatilize the solvent is also included.

[0030] In some embodiments, the drying temperature is 70° C. to 100° C., and the drying time is 10 h to 20 h.

[0031] According to another aspect of the present application, an embodiment of the present application provides a solid-state battery, which includes the composite solid-state electrolyte as described above or a composite solid-state electrolyte prepared according to the aforementioned method.

[0032] Implementing the technical solution of the present invention has at least the following beneficial effects:

[0033] In the embodiment of the present application, the composite solid electrolyte provided is provided with a coating layer on the surface of the electrolyte matrix, the coating layer includes a sulfone polymer, and also includes a lithium salt and / or an ionic liquid. Thus, by arranging a coating layer containing a sulfone polymer on the surface of an electrolyte matrix such as a sulfide electrolyte, a halide electrolyte, an oxide electrolyte, etc., the electrolyte can be made resistant to high voltage oxidation, that is, the oxidation resistance of the composite solid electrolyte is improved, the electrochemical window of the solid electrolyte material is widened, and the existing solid electrolytes such as sulfides are alleviated due to the narrow electrochemical window, and are easily oxidized at the positive electrode interface. The problem. At the same time, the coating layer also includes at least one of a lithium salt or an ionic liquid, and the high ionic conductivity of the lithium salt and / or the ionic liquid is utilized to effectively enhance the ionic conduction effect of the composite solid electrolyte, and alleviate the existing solid electrolyte and the positive electrode surface contact itself has a high interface resistance, resulting in a problem of high ionic conductivity.

[0034] The composite solid electrolyte of the present invention has good oxidation resistance and high ion conductivity, and the cycle performance of the solid-state battery assembled therewith can be significantly improved.

[0035] Additional aspects and advantages of the present application will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION

[0036] The present application is further described below in conjunction with specific embodiments. It should be understood that these embodiments of the present application are only used to illustrate the present application and are not used to limit the scope of the present application.

[0037] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range or the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0038] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0039] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0040] In some existing solid electrolytes, due to the narrow electrochemical window of solid electrolytes such as sulfides, they are easily oxidized at the positive electrode interface, generating an intermediate layer with low ion conductivity, increasing the interface impedance, and thus adversely affecting the battery's cycle performance. However, no effective solution has been proposed for the above problems.

[0041] Based on the above research, the inventors of this application have fully considered the characteristics of these existing solid electrolyte materials, and adopted a specific modification method to introduce a specific type of coating layer on the surface of the electrolyte matrix to improve the structural stability or oxidation resistance of the electrolyte material, or alleviate the problem of poor lithium ion conductivity of existing solid electrolytes, or alleviate the interface problem between the existing solid electrolyte membrane and the positive electrode, thereby improving the cycle performance of the battery. In view of this, the present application provides a composite solid electrolyte, a method for preparing a composite solid electrolyte, and a solid-state battery, and the present application is described in detail below.

[0042] [Composite solid electrolyte]

[0043] In some embodiments, a composite solid electrolyte is provided, the composite solid electrolyte comprising:

[0044] an electrolyte matrix comprising at least one of a sulfide electrolyte, a halide electrolyte, or an oxide electrolyte; and

[0045] The coating layer is coated on at least a portion of the surface of the electrolyte matrix, and the coating layer includes a sulfone polymer and a lithium salt and / or an ionic liquid.

[0046] In the present application, the composite electrolyte includes an electrolyte matrix and a coating layer coated on at least the surface of the electrolyte matrix; wherein the electrolyte matrix may be a sulfide electrolyte, or may be a halide electrolyte, or may be an oxide electrolyte, or may be a combination of any two of a sulfide electrolyte, a halide electrolyte and an oxide electrolyte, or may be a combination of a sulfide electrolyte, a halide electrolyte and an oxide electrolyte. Thus, by forming a coating layer on the surface of the electrolyte matrix of at least one of the above-mentioned sulfide electrolytes, halide electrolytes and oxide electrolytes, the problems of narrow electrochemical windows and poor ion conduction effects existing in these existing electrolytes can be effectively alleviated.

[0047] The coating layer includes a sulfone polymer and a lithium salt and / or an ionic liquid. As an example, the coating layer may include a sulfone polymer and a lithium salt; or, the coating layer may include a sulfone polymer and an ionic liquid; or, the coating layer may include a sulfone polymer, a lithium salt and an ionic liquid.

[0048] Optionally, the lithium salt is a molten salt, that is, a molten salt containing lithium.

[0049] In the present application, the term "coating" is not limited to direct coating, but also includes indirect coating. For example, the coating layer coats the electrolyte matrix, and there may be no other structure between the coating layer and the outer surface of the electrolyte matrix, or there may be one or more layers of other structures between the coating layer and the outer surface of the electrolyte matrix. Preferably, there is no other structure between the coating layer and the outer surface of the electrolyte matrix.

[0050] The coating layer is formed or coated on at least part of the surface of the electrolyte matrix, which can protect or improve the electrolyte matrix, and can be used to prevent the electrolyte matrix from directly contacting the air, improve the oxidation resistance of the electrolyte material, and improve the ion conduction effect of the electrolyte material and the structural stability of the electrolyte material. The coating layer is formed or coated on at least part of the surface of the electrolyte matrix, which means that the coating layer can completely encapsulate the electrolyte matrix in the coating layer, or the coating layer can only coat a part of the outer surface of the electrolyte matrix; that is, the coating layer can completely coat the electrolyte matrix, or can coat a part of the surface of the electrolyte matrix, preferably completely coat it.

[0051] The composite solid electrolyte provided is a core-shell structure, in which the core can adopt traditional sulfide electrolytes, halide electrolytes, oxide electrolytes and other electrolytes, and the outer shell or shell layer, that is, the coating layer, includes sulfone polymers, and lithium salts and / or ionic liquid coating materials, which can play an excellent protective or improvement role on the electrolyte matrix core material. The inventors of the present application have fully considered the intrinsic defects of the existing above-mentioned electrolyte matrix, and proposed a composite solid electrolyte material with high ion conductivity, and broadened the electrochemical window of the composite solid electrolyte material, effectively solving the interface problem between the solid electrolyte and the electrode. By modifying and coating it with a coating layer containing the above-mentioned coating material to form a core-shell structure, the oxidation resistance of the electrolyte matrix is ​​improved to a certain extent, the structural stability of the solid electrolyte is improved, and it can be beneficial to improve the ionic conductivity of the solid electrolyte, thereby improving the cycle performance of the battery. In detail:

[0052] In the present application, the coating formed on the surface of the electrolyte matrix includes sulfone polymers, and lithium salts and / or ionic liquids, wherein the sulfone polymers can be formed by free radical polymers. Furthermore, by arranging a coating containing sulfone polymers on the surface of electrolyte matrices such as sulfide electrolytes, halide electrolytes, oxide electrolytes, etc., the electrolyte can be made resistant to high voltage oxidation, that is, the oxidation resistance of the composite solid electrolyte is improved, the electrochemical window of the solid electrolyte material is widened, and the existing solid electrolytes such as sulfides are easily oxidized at the positive electrode interface due to the narrow electrochemical window. At the same time, the coating also includes at least one of lithium salts or ionic liquids, and the high ionic conductivity of lithium salts and / or ionic liquids is utilized to effectively improve the ionic conduction effect of the composite solid electrolyte, and the existing solid electrolyte and the positive electrode surface contact itself have a high interface resistance, resulting in a problem of high ionic conductivity.

[0053] Therefore, the present invention effectively improves the oxidation resistance of the electrolyte material and ensures the cycle stability of the battery by in-situ solidification of the sulfone-based polymer electrolyte interface on the surface of the electrolyte matrix. In addition, by in-situ polymerizing the molten salt and ionic liquid on the surface of the electrolyte matrix, the ion conduction effect of the electrolyte material is effectively improved, and the cycle performance of the assembled solid-state battery can be significantly improved.

[0054] In some embodiments, the electrolyte matrix includes but is not limited to any one of a sulfide electrolyte, a halide electrolyte or an oxide electrolyte or a combination of at least two thereof. The specific types of the above-mentioned sulfide electrolyte, halide electrolyte, and oxide electrolyte can adopt various specific types well known or conventional in the art. As an example, the sulfide electrolyte can be selected from at least one of a sulfide electrolyte of LGPS, a thio-LISICON structure, or a Li-Argyrodite type sulfide electrolyte.

[0055] The halide electrolyte can be selected from Li a -M-X6, Li a -M-X4, Li a - At least one of the M-X8 categories.

[0056] The oxide electrolyte may be selected from at least one of LATP, LLZTO or LLZO.

[0057] Of course, in other embodiments, other types of solid electrolytes may also be used as the electrolyte matrix, and the present application does not limit the specific types of sulfide electrolytes, halide electrolytes, and oxide electrolytes.

[0058] In some embodiments, the sulfone polymer can be formed by polymerizing a sulfone monomer, that is, the sulfone polymer can be formed by in-situ curing on the surface of the electrolyte matrix, and the raw materials for forming the sulfone polymer include a sulfone monomer (sulfone compound).

[0059] Optionally, the sulfone monomer includes, but is not limited to, any one or a combination of at least two of methyl vinyl sulfone, ethyl vinyl sulfone, phenyl vinyl sulfone, divinyl sulfone or phenyl vinyl sulfoxide. For the sake of brevity, the combinations within the above range are not listed one by one.

[0060] By using the above-mentioned sulfone monomers to form sulfone polymers and coating them on the surface of the electrolyte matrix, the prepared composite solid electrolyte can have excellent electrochemical properties, especially helping the electrolyte to resist high-voltage oxidation, that is, improving the oxidation resistance of the composite solid electrolyte and widening the voltage window of the solid electrolyte.

[0061] In some embodiments, the lithium salt comprises a fluorine-containing lithium salt.

[0062] In the present application, the lithium salt used is a molten salt, in particular, a molten salt containing lithium and fluorine.

[0063] As an example, the lithium salt includes, but is not limited to, any one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethylsulfonyl)imide, lithium oxalate, and lithium bis(trifluoromethylsulfonyl)imide, or a combination of at least two of them. For the sake of brevity, the combinations within the above range are not listed one by one.

[0064] Therefore, by adopting the above-mentioned lithium salts in combination with sulfone polymers and coating them on the surface of the electrolyte matrix, the prepared composite solid electrolyte can have excellent electrochemical properties, especially by utilizing the high ion conductivity of the above-mentioned lithium salts, which is beneficial to improve the ion conduction effect of the composite solid electrolyte, and can improve the interface problem between the solid electrolyte membrane and the positive electrode, effectively alleviating the problem of high interface resistance of the existing electrolyte when in contact with the positive electrode surface, resulting in low ion conductivity.

[0065] In some embodiments, the ionic liquid includes, but is not limited to, any one of or a combination of at least two of imidazole ionic liquids, quaternary amine ionic liquids, quaternary phosphonium ionic liquids, pyridine ionic liquids, pyrrolidine ionic liquids, or piperidine ionic liquids. For the sake of brevity, the combinations within the above range are no longer listed one by one.

[0066] As an example, the cation of the ionic liquid includes any one or a combination of at least two of quaternary ammonium salt ions, quaternary phosphonium salt ions, imidazolium salt ions and pyrrole salt ions. For the sake of brevity, the combinations within the above range are not listed one by one.

[0067] The anions of the ionic liquid include any one of halogen ions, tetrafluoroborate ions or hexafluorophosphate ions, or a combination of at least two of them. For the sake of brevity, the combinations within the above range are not listed one by one.

[0068] In some embodiments, the coating layer has a thickness of ≤ 500 nm.

[0069] Preferably, in some embodiments, the thickness of the coating layer is ≤200 nm.

[0070] As an example, the thickness of the coating layer may be 500 nm, 400 nm, 300 nm, 200 nm, 100 nm, 80 nm, 70 nm, 60 nm, 50 nm, 40 nm, 30 nm, 20 nm, 10 nm or less than 10 nm, etc.

[0071] In the present application, the thickness of the coating layer in the composite solid electrolyte can be measured by a method known in the art, for example, by a transmission electron microscope (TEM).

[0072] The thickness of the coating layer can be adjusted according to the size of the inner core of the electrolyte matrix. The appropriate thickness of the coating layer can not only ensure that the composite solid electrolyte has good processing performance, but also avoid the effect of excessive thickness and excessive coating material on the ionic conductivity and other properties of the composite solid electrolyte, or avoid the effect of too thin thickness to effectively exert the modification effect of the coating layer.

[0073] In some embodiments, in the composite solid electrolyte, the coating layer accounts for 0.1% to 50% by mass; that is, the coating layer accounts for 0.1% to 50% by mass in the composite solid electrolyte.

[0074] Preferably, in some embodiments, the mass proportion of the coating layer in the composite solid electrolyte is 0.5% to 10%.

[0075] As an example, the mass proportion of the coating layer in the composite solid electrolyte can be any point value among 0.1%, 1%, 1.5%, 2%, 2.5%, 3%, 4%, 5%, 6%, 8%, 10%, 12%, 14%, 15%, 18%, 20%, 25%, 30%, 35%, 40%, 50%, or a range value between any two of them.

[0076] By controlling the content of the coating layer within the above range, the excellent protection or improvement effect of the coating layer on the core material of the electrolyte matrix can be effectively exerted, and the excessive content of the coating layer can be avoided to affect the ionic conductivity and other properties of the composite solid electrolyte.

[0077] Therefore, the composite solid electrolyte provided by the present invention is a surface-modified electrolyte material, which can effectively improve the oxidation resistance of the electrolyte material, widen the electrochemical window of the electrolyte material, enhance the ion conduction effect of the electrolyte material, and alleviate the interface problems between the solid electrolyte and the electrode.

[0078] [Preparation method of composite solid electrolyte]

[0079] Accordingly, in some embodiments, the present application provides a method for preparing a composite solid electrolyte, the method comprising the following steps:

[0080] Providing a coating material solution, wherein the coating material solution includes a sulfone monomer, and a lithium salt and / or an ionic liquid;

[0081] The coating material solution is mixed with an electrolyte matrix, an initiator and a solvent, and after heating, stirring and drying, a coating layer is formed on at least the surface of the electrolyte matrix to obtain a composite solid electrolyte.

[0082] The method provided by the present invention can first prepare a coating material solution, then mix the prepared coating material solution with an electrolyte matrix, an initiator and a solvent, and after heating, stirring, drying and other treatments, a coating layer can be formed on the surface of the electrolyte matrix. Thus, the coating layer formed by this method effectively improves the oxidation resistance of the electrolyte material and ensures the cycle stability of the battery by in-situ solidification of a sulfone-based polymer electrolyte interface on the surface of the solid electrolyte; and effectively improves the ion conduction effect of the electrolyte material by in-situ polymerization of molten salt and ionic liquid on the surface of the solid electrolyte, and the cycle performance of the assembled solid-state battery is significantly improved.

[0083] The preparation method provided by the embodiment of the present invention has simple process, convenient operation, strong feasibility, and is easy to realize industrial application; in particular, the composite solid electrolyte prepared by this method can not only improve the structural stability or oxidation resistance of the material, but also ensure the ionic conductivity of the composite solid electrolyte.

[0084] It should be understood that all the features and advantages described above for the “composite solid electrolyte” are also applicable to the “method for preparing the composite solid electrolyte” and will not be described in detail here.

[0085] In some specific embodiments, the method for preparing the composite solid electrolyte specifically comprises the following steps (a) to (c):

[0086] (a) Preparation of coating material solution.

[0087] Optionally, the coating material solution is a lithium salt (molten salt)-sulfone solution with a concentration of 0.5 to 2 mol / L, that is, the coating material solution can be obtained by evenly mixing a lithium salt and a sulfone monomer (sulfone compound), for example, the above-mentioned coating material solution can be obtained by dissolving a lithium salt in a sulfone monomer.

[0088] Optionally, the coating material solution is an ionic liquid-sulfone solution with a concentration of 0.5 to 2 mol / L, that is, the coating material solution can be obtained by evenly mixing the ionic liquid and the sulfone monomer (sulfone compound), for example, the above-mentioned coating material solution can be obtained by dissolving the ionic liquid in the sulfone monomer.

[0089] Optionally, the coating material solution is a lithium salt, ionic liquid-sulfone solution with a concentration of 0.5 to 2 mol / L, that is, the coating material solution can be obtained by evenly mixing a lithium salt, an ionic liquid and a sulfone monomer (sulfone compound), for example, the above-mentioned coating material solution can be obtained by dissolving a lithium salt and an ionic liquid in a sulfone monomer.

[0090] Among them, the lithium salt is a molten salt containing lithium and fluorine; as an example, the lithium salt can be selected from any one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethylsulfonyl)imide, lithium oxalate, and lithium bis(trifluoromethylsulfonyl)imide, or a combination of at least two of them.

[0091] The sulfone monomer may be selected from any one or a combination of at least two of methyl vinyl sulfone, ethyl vinyl sulfone, phenyl vinyl sulfone, divinyl sulfone or phenyl vinyl sulfoxide.

[0092] The cation of the ionic liquid can be selected from any one or a combination of at least two of quaternary ammonium salt ions, quaternary phosphonium salt ions, imidazolium salt ions and pyrrole salt ions; the anion of the ionic liquid can be selected from any one or a combination of at least two of halogen ions, tetrafluoroborate ions or hexafluorophosphate ions.

[0093] The concentration range of the coating material solution is 0.5-2 mol / L, preferably 0.8-1.5 mol / L; as an example, the concentration of the coating material solution is 0.5 mol / L, 0.6 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.2 mol / L, 1.5 mol / L, 1.6 mol / L, 1.8 mol / L, 2 mol / L, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0094] (b) Preparing a mixture.

[0095] In step (b), preparing the mixture specifically comprises: mixing the coating material solution obtained in step (a) with the electrolyte matrix, the initiator and the solvent, and stirring under heating conditions to obtain a mixture.

[0096] In step (b), the coating material solution obtained in step (a) can be mixed evenly with the electrolyte matrix and the initiator, and then added to the solvent, and then subjected to subsequent heating, stirring and other treatments.

[0097] Among them, the added amount (mass) of the initiator can be 0.1% to 5% of the sulfone polymer, preferably 0.5% to 2%; for example, it can be any one of 0.1%, 0.2%, 0.5%, 0.8%, 1%, 1.5%, 2%, 3%, 4%, 5% or a range between any two of them.

[0098] The mass proportion of the coating material solution in the composite solid electrolyte is 0.5% to 50%, preferably 0.8% to 30%; for example, it can be any point value among 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 4%, 5%, 6%, 8%, 10%, 20%, 30%, 40%, 50%, or a range value between any two of them.

[0099] Optionally, the initiator includes, but is not limited to, any one of azobisisobutyronitrile, dimethyl azobisisobutyrate, azobisisoheptanenitrile, ammonium persulfate, benzoyl peroxide, tert-butyl benzoyl peroxide or methyl ethyl ketone peroxide, or a combination of at least two thereof. For the sake of brevity, the combinations within the above range are not listed one by one.

[0100] In some preferred embodiments, the initiator is selected from azobisisobutyronitrile.

[0101] Optionally, the solvent includes, but is not limited to, a nitrile organic solvent and / or an alcohol organic solvent, wherein the nitrile organic solvent includes any one or a combination of at least two of succinonitrile, adiponitrile, glutaronitrile or acetonitrile, and the alcohol organic solvent includes any one or a combination of at least two of methanol, ethanol, propanol or butanol. For the sake of brevity, the combinations within the above range are not listed one by one. Preferably, the alcohol organic solvent is selected from ethanol.

[0102] In some preferred embodiments, the solvent is selected from acetonitrile.

[0103] In some embodiments, in step (b), the conditions of heating and stirring include: stirring at a speed of 400 rpm to 1000 rpm for 10 h to 24 h in an environment with a dew point temperature below -50°C. The stirring speed may be, for example, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 1000 rpm, etc.; the stirring time may be, for example, 10 h, 11 h, 12 h, 14 h, 15 h, 16 h, 20 h, 24 h, etc.

[0104] It should be understood that the dew point temperature is actually the temperature at which water vapor and water reach equilibrium.

[0105] (c) post-treating the mixture.

[0106] In step (c), the post-treatment of the mixture specifically includes: heating (evaporating) the mixture obtained in step (b) to volatilize the solvent, and then placing the powder in a vacuum oven for drying to remove residual solvent and monomer; thereby obtaining a composite solid electrolyte material with a polymer electrolyte interface.

[0107] Optionally, in step (c), the drying temperature is 70°C to 100°C, and the drying time is 10h to 20h.

[0108] As an example, the drying temperature can be any one of 70°C, 80°C, 90°C, 100°C, or a range between any two of them; the heating treatment time can be any one of 10h, 11h, 12h, 14h, 15h, 16h, 18h, 20h, or a range between any two of them.

[0109] In some embodiments, the thickness of the coating layer is ≤500 nm. Preferably, the thickness of the coating layer is ≤200 nm.

[0110] Thus, the embodiments of the present invention effectively improve the oxidation resistance of the electrolyte material and ensure the cycle stability of the battery by in-situ solidifying the sulfone-based polymer electrolyte interface on the surface of the solid electrolyte; and effectively improve the ion conduction effect of the electrolyte material by in-situ polymerizing the molten salt and ionic liquid on the surface of the solid electrolyte, and the cycle performance of the assembled solid-state battery is significantly improved.

[0111] [Solid-state battery]

[0112] In some embodiments, the present application provides a solid-state battery, which includes the solid-state electrolyte as described above or a solid-state electrolyte prepared according to the aforementioned method.

[0113] Optionally, the solid-state battery can be an all-solid-state battery or a semi-solid-state battery, preferably an all-solid-state battery.

[0114] In some embodiments, the solid-state battery includes a positive electrode sheet, a negative electrode sheet and a solid electrolyte membrane, wherein one or more of the positive electrode sheet, the negative electrode sheet and the solid electrolyte membrane includes the composite solid electrolyte provided in any one of the above embodiments of the present application.

[0115] Preferably, the solid electrolyte membrane includes the composite solid electrolyte provided by any one of the above embodiments of the present application.

[0116] In some embodiments, in a solid-state battery, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector. As an example, the positive electrode current collector has two surfaces opposite to each other in its own thickness direction, and the positive electrode film layer is disposed on two opposite surfaces of the positive electrode current collector. It is understood that the positive electrode film layer can also be stacked on any one of the two surfaces of the positive electrode current collector.

[0117] In some embodiments, in a solid-state battery, the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector. As an example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode film layer is disposed on two opposite surfaces of the negative electrode current collector. It is understood that the negative electrode film layer can also be stacked on any one of the two surfaces of the negative electrode current collector.

[0118] Alternatively, in some embodiments, in a solid-state battery, the negative electrode sheet may be a lithium metal negative electrode.

[0119] The present application has no particular restrictions on the materials of the positive electrode current collector and the negative electrode current collector, as long as the purpose of the present application can be achieved, and can be selected according to actual needs. For example, in some embodiments, the positive electrode current collector and the negative electrode current collector can be aluminum, copper, nickel, stainless steel, iron, titanium or carbon, etc., and the shape is foil or mesh. Of course, in other embodiments, a composite current collector (such as an aluminum-carbon composite current collector or a copper-carbon composite current collector or a polymer and metal composite current collector) can also be used.

[0120] In some embodiments, in the positive electrode sheet, the positive electrode film layer includes a positive electrode active material, an electrolyte material, a conductive agent and a binder.

[0121] In some embodiments, in the negative electrode sheet, the negative electrode film layer includes a negative electrode active material, an electrolyte material, a conductive agent and a binder.

[0122] The present application adds electrolyte materials to the positive electrode film layer or the negative electrode film layer, and the lithium ion transmission in the electrode can be improved by adding the electrolyte materials.

[0123] In some embodiments, in the positive electrode film layer or the negative electrode film layer, the electrolyte material may be a halide electrolyte, a sulfide electrolyte, an oxide electrolyte, a polymer electrolyte, or any other solid electrolyte material known in the art.

[0124] It should be pointed out that the present invention has no particular restrictions on the types of positive electrode active materials, negative electrode active materials, conductive agents and binders in the positive electrode film layer and the negative electrode film layer, as long as the purpose of the present application can be achieved.

[0125] Optionally, in the positive electrode film layer, the mass ratio of the positive electrode active material, the electrolyte material, the conductive agent and the binder is (50-90): (1-50): (0.1-15): (0.1-15).

[0126] Optionally, in the negative electrode film layer, the mass ratio of the negative electrode active material, the electrolyte material, the conductive agent and the binder is (50-90): (1-50): (0.1-15): (0.1-15).

[0127] Since the solid-state battery provided in the embodiment of the present invention adopts all the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.

[0128] In order to better understand the present invention, the specific implementation process of the present invention will be described in detail below in a specific implementation mode. The implementation methods described below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application. If no specific technology or conditions are specified in the implementation method, the technology or conditions described in the literature in the field or the product specification shall be followed.

[0129] Example 1

[0130] The preparation of the composite solid electrolyte comprises the following steps:

[0131] (a) preparing a 1 mol / L coating material solution, wherein the coating material solution is a lithium salt-sulfone solution, wherein the lithium salt is lithium bistrifluoromethanesulfonyl imide (LiTFSI) and the sulfone monomer is methyl vinyl sulfone.

[0132] (b) Weigh a certain amount of sulfide solid electrolyte (Li6PS5Cl), the above-mentioned coating material solution and initiator azobisisobutyronitrile (AIBN), wherein the mass of the coating material solution is 1% of the mass of the composite solid electrolyte (in the composite solid electrolyte, the mass proportion of the coating layer is 1%), and the mass ratio of azobisisobutyronitrile is 1% of the mass of the sulfone polymer, add them into acetonitrile solvent and stir, and stir at a constant speed of 500 rpm for 12 hours in an environment where the dew point temperature is less than -50°C to obtain a mixture.

[0133] (c) The obtained mixture is heated to volatilize the solvent, and the obtained solid electrolyte powder is placed in a vacuum oven and dried at 80° C. for 12 h to obtain a composite solid electrolyte.

[0134] Example 2

[0135] The difference between Example 2 and Example 1 is that:

[0136] In step (b), the mass of the coating material solution is 4% of the mass of the composite solid electrolyte.

[0137] The rest are the same as in Example 1.

[0138] Example 3

[0139] The difference between Example 3 and Example 1 is that:

[0140] In step (b), the mass of the coating material solution is 6% of the mass of the composite solid electrolyte.

[0141] The rest are the same as in Example 1.

[0142] Example 4

[0143] The difference between Example 4 and Example 1 is that:

[0144] In step (b), the mass of the coating material solution is 8% of the mass of the composite solid electrolyte.

[0145] The rest are the same as in Example 1.

[0146] Example 5

[0147] The difference between Example 5 and Example 1 is that:

[0148] In step (b), the mass of the coating material solution is 10% of the mass of the composite solid electrolyte.

[0149] The rest are the same as in Example 1.

[0150] Example 6

[0151] The difference between Example 6 and Example 1 is that:

[0152] In step (b), the mass of the coating material solution is 20% of the mass of the composite solid electrolyte.

[0153] The rest are the same as in Example 1.

[0154] Example 7

[0155] The difference between Example 7 and Example 1 is that:

[0156] In step (b), the mass of the coating material solution is 30% of the mass of the composite solid electrolyte.

[0157] The rest are the same as in Example 1.

[0158] Example 8

[0159] The difference between Example 8 and Example 1 is that:

[0160] In step (b), the mass of the coating material solution is 40% of the mass of the composite solid electrolyte.

[0161] The rest are the same as in Example 1.

[0162] Example 9

[0163] The difference between Example 9 and Example 1 is that:

[0164] In step (b), the mass of the coating material solution is 50% of the mass of the composite solid electrolyte.

[0165] The rest are the same as in Example 1.

[0166] Example 10

[0167] The difference between Example 10 and Example 1 is that:

[0168] In step (a), the lithium salt is lithium bis(fluorosulfonyl)imide (LiFSI), and the sulfone monomer is phenyl vinyl sulfone. The rest is the same as in Example 1.

[0169] Embodiment 11

[0170] The difference between Example 11 and Example 1 is that:

[0171] (a) preparing a 1 mol / L coating material solution, wherein the coating material solution is an ionic liquid-sulfone solution, wherein the cation of the ionic liquid is a quaternary ammonium salt ion, the anion is a halogen ion, and the sulfone monomer is methyl vinyl sulfone.

[0172] The rest are the same as in Example 1.

[0173] Example 12

[0174] The difference between Example 12 and Example 11 is that:

[0175] In step (b), the mass of the coating material solution is 4% of the mass of the composite solid electrolyte.

[0176] The rest is the same as Example 11.

[0177] Example 13

[0178] The difference between Example 13 and Example 11 is that:

[0179] In step (b), the mass of the coating material solution is 6% of the mass of the composite solid electrolyte.

[0180] The rest is the same as Example 11.

[0181] Embodiment 14

[0182] The difference between Example 14 and Example 11 is that:

[0183] In step (b), the mass of the coating material solution is 8% of the mass of the composite solid electrolyte.

[0184] The rest is the same as Example 11.

[0185] Embodiment 15

[0186] The difference between Example 15 and Example 11 is that:

[0187] In step (b), the mass of the coating material solution is 10% of the mass of the composite solid electrolyte.

[0188] The rest is the same as Example 11.

[0189] Example 16

[0190] The difference between Example 16 and Example 11 is that:

[0191] In step (b), the mass of the coating material solution is 20% of the mass of the composite solid electrolyte.

[0192] The rest is the same as Example 11.

[0193] Embodiment 17

[0194] The difference between Example 17 and Example 11 is that:

[0195] In step (b), the mass of the coating material solution is 30% of the mass of the composite solid electrolyte.

[0196] The rest is the same as Example 11.

[0197] Embodiment 18

[0198] The difference between Example 18 and Example 11 is that:

[0199] In step (b), the mass of the coating material solution is 40% of the mass of the composite solid electrolyte.

[0200] The rest is the same as Example 11.

[0201] Embodiment 19

[0202] The difference between Example 19 and Example 11 is that:

[0203] In step (b), the mass of the coating material solution is 50% of the mass of the composite solid electrolyte.

[0204] The rest is the same as Example 11.

[0205] Embodiment 20

[0206] The difference between Example 20 and Example 11 is that:

[0207] In step (a), the cation of the ionic liquid is an imidazolium ion, the anion is a tetrafluoroborate ion, and the sulfone monomer is divinyl sulfone.

[0208] The rest is the same as Example 11.

[0209] Comparative Example 1

[0210] Existing sulfide solid electrolyte (Li6PS5Cl).

[0211] Comparative Example 1 uses an untreated solid electrolyte material known in the prior art.

[0212] Performance Testing

[0213] 1. The solid electrolytes obtained in the above embodiments and comparative examples were subjected to performance tests.

[0214] Ion conductivity test: The impedance of the solid electrolyte was tested using the VSP electrochemical workstation from Biologic, France. The perturbation voltage was 10mV, the frequency range was 1MHZ-10mHZ to test the impedance of the electrolyte, and the conductivity was calculated using the formula σ=d / (S*R).

[0215] The test results are shown in Table 1.

[0216] 2. The solid electrolytes obtained from some of the above examples and comparative examples are assembled into all-solid-state batteries. Specifically:

[0217] (1) Preparation of positive electrode sheet: 8g of positive electrode active material NCM955, 1.65g of solid electrolyte Li6PS5Cl, 0.2g of binder polyvinylidene fluoride (PVDF) and 0.15g of conductive agent vapor-grown carbon fiber (VGCF) are added to 10mL of solvent xylene and stirred. For example, in an environment where the dew point temperature is less than -50°C, the stirrer is stirred at a constant speed of 500rpm for 5 hours to obtain a slurry. The above-prepared slurry is coated on the current collector aluminum foil, and then dried in an oven at 90°C for 12 hours. The dew point temperature of the environment in which the electrode sheet is located should be kept below -50°C during the drying process, or nitrogen should be filled in this environment for protection. After the organic solvent in the electrode sheet is completely evaporated, the electrode sheet is cooled to room temperature and taken out of the oven to obtain a positive electrode sheet.

[0218] (2) Preparation of negative electrode sheet: 7g of negative electrode active material graphite, 2.65g of solid electrolyte Li6PS5Cl, 0.2g of binder polyvinylidene fluoride (PVDF) and 0.15g of conductive agent vapor-grown carbon fiber (VGCF) are added to 10mL of solvent xylene and stirred. For example, in an environment where the dew point temperature is less than -50°C, the stirrer is stirred at a constant speed of 500rpm for 5 hours to obtain a slurry. The above-prepared slurry is coated on the current collector copper foil, and then dried in an oven at 90°C for 12 hours. The dew point temperature of the environment in which the electrode sheet is located should be kept below -50°C during the drying process, or nitrogen should be filled in this environment for protection. After the organic solvent in the electrode sheet is completely evaporated, the electrode sheet is cooled to room temperature and taken out of the oven to obtain a negative electrode sheet.

[0219] (3) Preparation of solid electrolyte membrane: 4.9g of solid electrolyte, 0.1g of binder SEBS, and 3.1g of xylene are stirred and mixed. For example, in an environment where the dew point temperature is less than -50°C, the agitator is stirred at a constant speed of 500rpm for 5 hours to obtain a slurry. The slurry prepared above is coated on an aluminum foil, and then dried in an oven at 90°C for 12 hours. The dew point temperature of the electrode environment should be kept below -50°C during the drying process, or nitrogen should be filled into the environment for protection. After the organic solvent in the electrode is completely evaporated, the electrode is cooled to room temperature and taken out of the oven to obtain a solid electrolyte membrane.

[0220] (4) Battery assembly: Under a pressure of 100 MPa, the solid electrolyte membrane is transferred to the surface of the positive electrode, and then the negative electrode is close to the side of the solid electrolyte membrane. It is pressed into a finished product under a pressure of 500 MPa and encapsulated with an aluminum-plastic film to obtain a finished battery.

[0221] The assembled solid-state battery is then subjected to electrochemical performance tests, including:

[0222] Cycle performance test: The prepared all-solid-state battery was subjected to charge and discharge tests under 0.1C conditions to obtain the number of cycles and capacity retention rate (%).

[0223] The test results are shown in Table 2 below.

[0224] Table 1 Ionic conductivity test results of composite solid electrolytes in various embodiments and comparative examples

[0225] Example Ionic conductivity (mS / cm) Example 1 4.93 Example 2 5.09 Example 3 5.51 Example 4 5.60 Example 5 5.76 Example 6 5.42 Example 7 4.51 Example 8 4.49 Example 9 4.33 Example 10 5.51 Embodiment 11 5.74 Example 12 5.86 Example 13 5.95 Embodiment 14 5.96 Embodiment 15 6.46 Example 16 6.09 Embodiment 17 5.15 Example 8 4.30 Embodiment 19 4.17 Embodiment 20 4.98 Comparative Example 1 3.80

[0226] It can be seen from Table 1 that, compared with Comparative Example 1, the composite solid electrolytes prepared in Examples 1-20 of the present invention have higher ionic conductivity.

[0227] Table 2 Electrochemical performance test of solid-state batteries prepared in some embodiments and comparative examples

[0228]

[0229]

[0230] It can be seen from Table 2 that, compared with Comparative Example 1, the solid-state battery prepared using the composite solid-state electrolyte of the embodiment of the present invention has better cycle performance.

[0231] Parts of the present invention that are not described in detail are well known to those skilled in the art.

[0232] The basic principle of the present invention is described above in conjunction with specific embodiments. However, it should be pointed out that the advantages, strengths, effects, etc. mentioned in the present invention are only examples and not limitations, and it cannot be considered that these advantages, strengths, effects, etc. must be possessed by each embodiment of the present invention. In addition, the specific details disclosed above are only for the purpose of illustration and facilitation of understanding, rather than limitation, and the above details do not limit the present invention to being implemented by adopting the above specific details.

[0233] It should be noted that the term "and / or" or " / " used in this document is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The singular forms of "a", "the" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0234] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0235] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A composite solid electrolyte, characterized in that: The composite solid electrolyte comprises: an electrolyte matrix, the electrolyte matrix comprising at least one of a sulfide electrolyte, a halide electrolyte, or an oxide electrolyte; and The coating layer is coated on at least a portion of the surface of the electrolyte matrix, the coating layer comprises a sulfone polymer, and the coating layer further comprises a lithium salt and / or an ionic liquid.

2. The composite solid electrolyte according to claim 1, characterized in that The sulfone polymer is formed by polymerizing a sulfone monomer, and the sulfone monomer includes at least one of methyl vinyl sulfone, ethyl vinyl sulfone, phenyl vinyl sulfone, divinyl sulfone or phenyl vinyl sulfoxide.

3. The composite solid electrolyte according to claim 1, characterized in that The lithium salt comprises a fluorine-containing lithium salt; and / or, The ionic liquid includes at least one of imidazole ionic liquids, quaternary amine ionic liquids, quaternary phosphonium ionic liquids, pyridine ionic liquids, pyrrolidine ionic liquids or piperidine ionic liquids.

4. The composite solid electrolyte according to claim 3, characterized in that: The lithium salt comprises at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethylsulfonyl)imide, lithium oxalate and lithium bis(trifluoromethylsulfonyl)imide; and / or, The cation of the ionic liquid includes at least one of quaternary ammonium salt ion, quaternary phosphonium salt ion, imidazolium salt ion and pyrrole salt ion, and the anion of the ionic liquid includes at least one of halogen ion, tetrafluoroborate ion or hexafluorophosphate ion.

5. The composite solid electrolyte according to any one of claims 1 to 4, characterized in that: The thickness of the coating layer is ≤500nm; and / or, In the composite solid electrolyte, the coating layer accounts for 0.1% to 50% by mass.

6. A method for preparing a composite solid electrolyte, characterized in that: The method comprises the following steps: Providing a coating material solution, wherein the coating material solution includes a sulfone monomer, and a lithium salt and / or an ionic liquid; The coating material solution is mixed with an electrolyte matrix, an initiator and a solvent, and after heating, stirring and drying, a coating layer is formed on at least the surface of the electrolyte matrix to obtain a composite solid electrolyte.

7. The method for preparing a composite solid electrolyte according to claim 6, characterized in that: The concentration of the coating material solution is 0.5 to 2 mol / L; and / or, The sulfone monomer includes at least one of methyl vinyl sulfone, ethyl vinyl sulfone, phenyl vinyl sulfone, divinyl sulfone or phenyl vinyl sulfoxide; and / or, The lithium salt comprises a fluorine-containing lithium salt; and / or, The ionic liquid includes at least one of imidazole ionic liquids, quaternary amine ionic liquids, quaternary phosphonium ionic liquids, pyridine ionic liquids, pyrrolidine ionic liquids or piperidine ionic liquids.

8. The method for preparing a composite solid electrolyte according to claim 6, characterized in that: The initiator comprises at least one of azobisisobutyronitrile, dimethyl azobisisobutyrate, azobisisoheptanenitrile, ammonium persulfate, benzoyl peroxide, tert-butyl benzoyl peroxide or methyl ethyl ketone peroxide; and / or, The solvent includes a nitrile organic solvent and / or an alcohol organic solvent, wherein the nitrile organic solvent includes at least one of succinonitrile, adiponitrile, glutaronitrile or acetonitrile, and the alcohol organic solvent includes at least one of methanol, ethanol, propanol or butanol; and / or, The heating and stirring conditions include: stirring at a rotation speed of 400 rpm to 1000 rpm for 10 hours to 24 hours in an environment where the dew point temperature is lower than -50°C.

9. The method for preparing a composite solid electrolyte according to claim 6, characterized in that: After the heating and stirring and before the drying, a step of heating to volatilize the solvent is also included; and / or, The drying temperature is 70° C. to 100° C., and the drying time is 10 h to 20 h.

10. A solid-state battery, characterized in that: The solid-state battery comprises the composite solid-state electrolyte according to any one of claims 1 to 5, or comprises the composite solid-state electrolyte prepared by the method according to any one of claims 6 to 9.

Citation Information

Cited By

  • Multifunctional graft polymer coated sulfide solid electrolyte and preparation method thereof

    CN121812700A